Proses berfikir kreatif siswa kelas viii dalam memecahkan masalah berdasarkan teori hayes ditinjau dari gaya kognitif dan jenis kelamin - Masfufah, Masfufah; Iffah , Jauhara Dian Nurul; Nurwiani, Nurwiani (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
The aim of this research is to describe the creative thinking process of male and female students with field dependent (FD) and field independent (FI) cognitive styles in solving mathematical problems based on Hayes' theory. This research is a descriptive study with the subjects being two male and two female students in class VIII MTs Darul Ulum Bandung, each of whom has FD and FI cognitive styles. The results of the research show that male FD students' creative thinking is based on flexibility, visible steps in planning solutions, being able to explain the various strategies used, originality, visible steps in implementing plans, determining new strategies in solving problems according to their own opinion, elaboration, visible steps in evaluating plans and evaluating results. , provide an assessment of problem solving planning. The results of the research show that the creative thinking of female FD students, namely originality, shows the steps in implementing the plan, and can determine new strategies in solving problems according to their own opinion. elaboration There are steps to evaluate plans and evaluate solutions, provide assessments on problem solving plans so that ideas are more detailed and provide assessments of problem solving results. The results of the research show that male FI students think creatively in all aspects, namely the fluency aspect, the flexibility aspect, the originality aspect, Elaboration aspect. The research results show that students think creatively Women's FI, namely in all aspects, namely the fluency aspect, flexibility aspect, originality aspect, elaboration aspect